Fast software implementation of des for lightweight platforms - Özkaynak, Fatih; Muhamad, Mukhlis I. (Institute of Electrical and Electronics Engineers Inc., 2017)
Many services are being moved to digital environments with industry 4.0. however, But the information in the digital environment poses a great risk. Ensuring the security of information on the users of online applications is a necessity. This perspective requires safe signal processing. But it is difficult to guarantee safe signal processing for resource constrained devices. Lightweight cryptology, which has been on the agenda in recent years, has emerged to solve this problem. While designers of lightweight cryptographic algorithms try to reduce the hardware requirements, they ignore software implementation of lightweight protocols. This study presents new design architecture for improving the software implementation of the DES. In the study, two different acceleration techniques will be used to speed up the DES algorithm in software. The results show that the developed code is faster than original DES. © 2017 IEEE.
2017 International Artificial Intelligence and Data Processing Symposium, IDAP 2017 -- 16 September 2017 through 17 September 2017 -- Malatya -- 115012
Keywords: DES; Information security; Lightweight cryptography; Software implementation